2001
DOI: 10.1093/arclin/16.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Detecting change: A comparison of three neuropsychological methods, using normal and clinical samples

Abstract: Detecting change in individual patients is an important goal of neuropsychological testing. However, limited information is available about test-retest changes, and well-validated prediction methods are lacking. Using a large nonclinical subject group (N = 384), we recently investigated test-retest reliabilities and practice effects on the Wechsler Adult Intelligence Scale and Halstead-Reitan Battery. Data from this group also were used to develop models for predicting follow-up test scores and establish confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(100 citation statements)
references
References 14 publications
5
95
0
Order By: Relevance
“…A recent review paper [52] reported that a comparative study in neurologically stable patients found that regression models were better able to predict outcomes than the use of the RCI and produced narrower confidence intervals [53][54][55][56]. Vardy et al recommended either a regression model or the RCI to analyze longitudinal data in this area of study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review paper [52] reported that a comparative study in neurologically stable patients found that regression models were better able to predict outcomes than the use of the RCI and produced narrower confidence intervals [53][54][55][56]. Vardy et al recommended either a regression model or the RCI to analyze longitudinal data in this area of study.…”
Section: Discussionmentioning
confidence: 99%
“…In fact it is likely that the variance of change scores in the patient group is larger than in the control group due to different individual responses to chemotherapy. We feel justified in using reliable change indices with correction for practice (see Heaton et al for a comparison of RCI and other methods of detecting change [15]). While we feel justified in the method we have selected the fact remains that those employed by other researchers produce very different results.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the prediction of dementia is the only question to be answered (which it is usually not) and when it is at the same time of no interest, whether the patient has reliably changed in cognition, then the computation of RCI does not seem essential. This does not exclude the possibility that RCI are useful for other clinical questions than dementia diagnosis (see e. g. [7]). …”
Section: Discussionmentioning
confidence: 99%
“…Two earlier studies only investigated an RCI that corrected for practice effects [7,14]. Generally, it seems important that the absolute level of test performance is accounted for (see also [7]). If the RCI+regression is computed, the cognitive level is automatically accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation